Rsf-1/HBXAP overexpression is independent of gene amplification and is associated with poor outcome in patients with urinary bladder urothelial carcinoma. Issue 9 (9th June 2012) - Liang, Peir-In; Wu, Li-Ching; Sheu, Jim Jinn-Chyuan; Wu, Ting-Feng; Shen, Kun-Hung; Wang, Yu-Hui; Wu, Wen-Ren; Shiue, Yow-Ling; Huang, Hsuan-Ying; Hsu, Han-Ping; Chen, Yi-Hsien; Chen, Li-Tzon; et al.
Abstract : Backgrounds: Urothelial carcinoma of the urinary bladder (UCUB) is prevalent in developed countries. It often shows genetic instability and is associated with amplification (or gain) of various oncogenic genes or suppressive genes. Rsf-1, a subunit of ATP-dependent chromatin-remodelling complexes that mediates ATPase-dependent chromatin remodelling, confers tumour aggressiveness in certain carcinomas. The authors evaluate the Rsf-1 gene and expression status and its associations with clinicopathological features and survival in their UCUB collection. Methods: Immunohistochemistry was used to assess the Rsf-1 expression profile in 295 UCUB specimens, and was found to correlate with clinicopathological data. Real-time RT-PCR and fluorescence in situ hybridisation were used to detect RSF-1 mRNA expression and gene dosage in 20 independent cases. Western blot analysis was used to evaluate Rsf-1 protein expression in human urothelial cell lines. Results: Rsf-1 overexpression was demonstrated in 101 cases (34.2%), and was significantly associated with advanced primary tumour (p<0.001), nodal metastasis (p=0.004), higher histological grades (p=0.001) and frequent mitoses (p<0.001). Moreover, it was predictive in disease-specific survival and metastasis-free survival in both univariate and multivariate analyses (p<0.0001 for both). Although RSF-1 gene amplification can be barely detected, its mRNA expression is significantly enhanced in tumours with higher primary tumour (p=0.041) and positive nodal statuses (p=0.010), respectively. Rsf-1 protein was abundant in invasive urothelial carcinoma cells but was not benign. Conclusions: Overexpression of Rsf-1 is associated with higher tumour stage and poorer clinical outcome. The current study by the authors suggests gene amplification-independent mechanisms driving Rsf-1 overexpression during UCUB tumour progression.